Study of Land's Carrying Capacity on The Availability and Need For Staple Foods in The City of Mataram - Rusdiani, Rusdiani; Suwardji, Suwardji; Mulyati, Mulyati (Jurnal Biologi Tropis, 2024)
Increasing the area of rice fields, harvest area, planting area, rice productivity and rice production can increase the availability of staple foods. This aims of this study 1) to analyze the carrying capacity of agricultural land in supporting food security in Mataram City. 2) to determine the availability and need for staple food (rice) in Mataram City. The research method used quantitative descriptive methods using secondary data from the Central Statistics Agency of City of Mataram and other related agencies in Mataram City in 2023. Data was analysed using land carrying capacity analysis and analysis of the availability and demand for rice in the City of Mataram. The results of the research showed that 1) the carrying capacity of agricultural land in the City of Mataram is 0.0231 or less than 1, meaning that the need for rice in the City of Mataram has not been able to be met from the existing agricultural land area and the current rice production, 2) The availability of rice in the City Mataram in 2023 is 13,510.83 tonnes, while the demand for rice is 67,980.76 tonnes, resulting in a shortage (deficit) of rice demand of 54,469.93 tonnes or a deficit in rice availability of 400%.